Fixed Point Theorems for Generalized $F-$contraction on Metric Space - Barman, Dinanath; Tiwary, Kalishankar (Sarajevo Journal of Mathematics, 2022)
In this paper, we have generalized $F-$contraction to $MF-$contraction, a new of notation in metric space and we have proved some results with examples and corollaries.